IDENTIFIKASI JIWA KEWIRAUSAHAAN PESERTA DIDIK SETELAH MENGIKUTI PROYEK MATA PELAJARAN BIOLOGI DI SMA NEGERI 1 GUGUAK - Fitri, Rahmadhani; Kholila, Azhari; Arsih, Fitri; Helendra; Anggriyani, Ria (Universitas Cokroaminoto Palopo, 2024)
Based on BPS data in 2022, the second highest unemployment rate in 2021-2022 was high school graduates. This is partly due to the lack of provision of survival skills/life skills for students to face challenges in the future. The Merdeka Curriculum is a curriculum that can provide life skills and develop students' character. One of the skills that is very much needed by high school students is the skill to create opportunities and turn those opportunities into something valuable. This is closely related to the entrepreneurial spirit and attitude. Project-based learning has a major influence in honing the entrepreneurial spirit of students. This study aims to determine the level of entrepreneurial spirit of students after participating in the biology subject project at SMA Negeri 1 Guguak.This type of research is quantitative descriptive research. The research instrument used is a questionnaire. The research instrument used has been validated by two lecturers from the Department of Biology, FMIPA UNP and was tested on 30 students outside the research sample. The sample in this study were students in grades XI and XII with a total of 231 students at SMA Negeri 1 Guguak in the 2024/2025 academic year. The questionnaire distributed was an entrepreneurial spirit questionnaire after participating in a biology subject project. The research data were analyzed using percentage analysis (%) of student answers. Based on the research conducted, the value of students' entrepreneurial spirit after participating in a biology subject project was 79.50% and was included in the good category. It can be concluded that after participating in a biology subject project, it can foster students' entrepreneurial spirit which is identified through 6 main indicators, namely self-confidence, task and result orientation, daring to take risks, leadership, originality, and future orientation.